Getting an information security job for dummies - Gregory, Peter H. (Hoboken, New Jersey : John Wiley and Sons, Inc., 2015)
Looking for a great job in a booming field? Information security is the first thing you need to know, and Gregory gives you tips on technical requirements, creating your resume, what to do after the interview, and much more. You'll get a peek inside different InfoSec jobs, and look at the pros and cons of working for security vendors, private companies, or the government.
Introduction -- So you want to be an InfoSec professional -- Having the right stuff -- Finding a job with the right organization -- Getting hired! -- The part of tens.
Includes index.
Keywords: Computer security -- Vocational guidance; Computer networks -- Security measures -- Vocational guidance; Computer crimes -- Prevention -- Vocational guidance